Perancangan Sistem Informasi Kepegawaian Pada PT Elco Prima Sejahtera - Stevanus, Andry; Mardiani, Mardiani (Universitas Multi Data Palembang, 2025)
PT Elco Prima Sejahtera is a company established in 1998 and based in Palembang, engaged in providing products and services to National Oil and Gas Companies, with a total of 41 employees. The existing system at PT. Elco Prima Sejahtera is less than optimal because it still uses paper, Microsoft Word, WhatsApp, and email, making searches time-consuming, prone to errors, and even resulting in lost documents. In the development of the system, the RUP (Rational Unified Process) method was used, involving interviews and literature studies. The system design is built using PHP with the Laravel framework and MySQL as the database. The Employee Information System will record employee data consisting of attendance data, recruitment, leave, rewards and punishments, promotions, and demotions. With the presence of the employee information system, it can address the issues at PT Elco Prima Sejahtera.